Cancer pain: where are we now?. (5th December 2018) - Magee, David; Bachtold, Sabina; Brown, Matthew; Farquhar-Smith, Paul
Increasing numbers of those living with and beyond cancer presents a clinical challenge for pain specialists. A large proportion of these patients experience pain secondary to their disease or its treatment, impeding rehabilitation and significantly impacting upon their quality of life. The successful management of this pain presents a considerable challenge. This review aims to outline current concepts and treatment options, while considering nuances within pain assessment and the use of large-scale data to help guide further advances.